2014
DOI: 10.1007/s11425-014-4801-7
|View full text |Cite
|
Sign up to set email alerts
|

Ruan’s conjecture on singular symplectic flops of mixed type

Abstract: We prove that the orbifold quantum ring is preserved under singular symplectic flops. Hence we verify Ruan's conjecture for this case. Contents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In this case, the celebrated Crepant Transformation Conjecture of Y. Ruan predicts that the quantum (orbifold) cohomology algebras of X + and X − should be related by analytic continuation in the quantum parameters. This conjecture has stimulated a great deal of interest in the connections between quantum cohomology (or Gromov-Witten theory) and birational geometry: see, for example, [9,10,18,19,21,23,24,28,41,45,53,[56][57][58][59]62,68,71,75,76]. Ruan's original conjecture was subsequently refined, revised, and extended to higher genus Gromov-Witten invariants, first by Bryan-Graber [20] under some additional hypotheses, and then by Coates-Iritani-Tseng, Iritani, and Ruan in general [34,35,50].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the celebrated Crepant Transformation Conjecture of Y. Ruan predicts that the quantum (orbifold) cohomology algebras of X + and X − should be related by analytic continuation in the quantum parameters. This conjecture has stimulated a great deal of interest in the connections between quantum cohomology (or Gromov-Witten theory) and birational geometry: see, for example, [9,10,18,19,21,23,24,28,41,45,53,[56][57][58][59]62,68,71,75,76]. Ruan's original conjecture was subsequently refined, revised, and extended to higher genus Gromov-Witten invariants, first by Bryan-Graber [20] under some additional hypotheses, and then by Coates-Iritani-Tseng, Iritani, and Ruan in general [34,35,50].…”
Section: Introductionmentioning
confidence: 99%
“…In [3,4], the authors initiated a program for studying quantum cohomology under birational transformation of orbifolds. In their papers, they considered the singularity W r = {(x, y, z, t) | xy − z 2r + t 2 }/µ r (a, −a, 1, 0) with r being a prime number.…”
Section: Introduction In [18]mentioning
confidence: 99%
“…They showed that Ruan cohomology is invariant under orbi-flops. Then, by using relative orbifold Gromov-Witten invariants and degeneration formulas, they proved that quantum cohomology is invariant under orbi-flops in [4].…”
Section: Introduction In [18]mentioning
confidence: 99%
“…The Crepant Transformation Conjecture has been verified to various extents of generalities and has become a guiding principle in the study of the relation between quantum cohomology and birational geometry. See for instance [3,4,10,11,13,[16][17][18][19][21][22][23]36,38,41,[45][46][47][48][49][50][51]57]. It has received particular success in the toric setting, where most required ingredients have explicit descriptions.…”
mentioning
confidence: 99%